2012
DOI: 10.1586/erc.12.49
|View full text |Cite
|
Sign up to set email alerts
|

The older patient with heart failure: high risk for frailty and cognitive impairment

Abstract: Managing older heart failure (HF) patients can be complicated by both cardiac and noncardiac conditions. Over the past 20 years, care for HF patients has become more complex, with a rising proportion of older people living with HF. In particular, cognitive impairment (CI) and frailty often coexist with HF in the elderly. With the prevalence of HF, frailty and cognitive impairment rising with age, the simultaneous occurrence of at least two of these conditions in the same individual will become more frequent. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 208 publications
(183 reference statements)
0
23
1
3
Order By: Relevance
“…Prior work has suggested that perhaps the best method for assessing frailty should depend upon the therapy being considered (14), but this remains open to debate. Moreover, while we know poor nutrition and frailty are associated with worse outcomes (15, 16), it is unclear how helpful nutritional supplements are in rectifying these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has suggested that perhaps the best method for assessing frailty should depend upon the therapy being considered (14), but this remains open to debate. Moreover, while we know poor nutrition and frailty are associated with worse outcomes (15, 16), it is unclear how helpful nutritional supplements are in rectifying these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Полученные в нашем исследовании результаты мо-гут свидетельствовать о том, что одной из причин снижения приверженности к лечению у больных ИБС и ХСН старших возрастных групп являются нарушения памяти [4,9]. Помимо этого причинами невнимательного отношения к времени приема ле-карства и пропуска приема лекарства при хорошем самочувствии, по данным литературы, могут быть недостаточная информированность о своем заболе-вании, способах его лечения и важности проводи-мой терапии, стоимость назначенных препаратов при необходимости их длительного применения, сложность схемы применения препаратов, а также опасение побочного действия принимаемых препа-ратов [1,2,8].…”
Section: показательunclassified
“…Наиболее до-ступным в клинической практике методом оценки приверженности к лечению является применение опросников [7,11,13]. В ряде исследований про-демонстрировано снижение приверженности те-рапии у лиц старших возрастных групп [2,7,8,9]. В этой связи представляется важной оценка влия-ния приверженности у этой категории пациентов с ХСН на структурно-функциональные изменений миокарда.…”
Section: Introductionunclassified
“…Functional and cognitive impairments are commonly seen in older patients with HF [35], and those selected for SNF admission after hospitalization often have additional functional limitations compounded by frailty. Acute illness with ensuing hospitalization can lead to a dynamic course of declining physical function, and in general, only 30 % of older patients discharged from the hospital with a new disability will return to their prior level of functioning [36].…”
Section: Introductionmentioning
confidence: 99%